Comprehensive Physiology 2012
DOI: 10.1002/cphy.c080111
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Function During Anesthesia: Effects on Gas Exchange

Abstract: Anaesthesia causes a respiratory impairment, whether the patient is breathing spontaneously or is ventilated mechanically. This impairment impedes the matching of alveolar ventilation and perfusion and thus the oxygenation of arterial blood. A triggering factor is loss of muscle tone that causes a fall in the resting lung volume, functional residual capacity. This fall promotes airway closure and gas adsorption, leading eventually to alveolar collapse, that is, atelectasis. The higher the oxygen concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 258 publications
2
88
0
1
Order By: Relevance
“…20,21 The functional residual capacity of anesthetized patients decreases in part due to a decrease in respiratory muscle tone, resulting in a new lung-chest wall equilibrium at a lower overall volume of the respiratory system. 22 There is also a cranial displacement of the diaphragm that occurs during general anesthesia and in the supine position that contributes to atelectasis formation especially in obese patients, because the abdominal content that is displaced is of tremendous weight (Fig. 1).…”
Section: Physiological Characteristics Of the Respiratory System Durimentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The functional residual capacity of anesthetized patients decreases in part due to a decrease in respiratory muscle tone, resulting in a new lung-chest wall equilibrium at a lower overall volume of the respiratory system. 22 There is also a cranial displacement of the diaphragm that occurs during general anesthesia and in the supine position that contributes to atelectasis formation especially in obese patients, because the abdominal content that is displaced is of tremendous weight (Fig. 1).…”
Section: Physiological Characteristics Of the Respiratory System Durimentioning
confidence: 99%
“…24 Lung mechanics are also impaired in the atelectatic lung, because the lung is less compliant at lower volumes. 22 In normal-weight anesthetized subjects, Rothen et al 25 showed by chest CT imaging that atelectasis is enhanced by the use of 1.0 F IO 2 during preoperative induction compared with the use of 0.3 F IO 2 as a result of absorption atelectasis. Lower oxygen concentrations might reduce the formation of atelectasis but also shorten the safe apnea period during intubation.…”
Section: Physiological Characteristics Of the Respiratory System Durimentioning
confidence: 99%
“…Macroscopically, atelectasis will be more easily produced during anesthesia and postoperatively when breathing hyperoxic gas (77,78). Thus, atelectasis is caused by absorption of alveolar gas, and oxygen is the gas that is absorbed the fastest since it is being consumed in the body.…”
Section: * * * Göran Hedenstiernamentioning
confidence: 99%
“…Again, there is not space enough here to deal with these issues, but the interested reader is referred to the review article of Hedenstierna and Rothen. 8 Different steps can be taken to improveV=Q matching and will be discussed as follows:…”
mentioning
confidence: 99%